Assessment of Percutaneous Pedicle Screw Fixation in Management of Traumatic Thoracolumbar Spine Fractures; Local Study at Suez Canal University Hospital - Mohamed Hasanein (Egyptian Spine Association, 2017)
Background Data: Management of thoracolumbar fractures using the traditional posterior approach is associated with extensive paravertebral muscles damage and high postoperative morbidity. Minimally invasive percutaneous pedicle screw fixation is a highly valuable alternative for minimizing approach related morbidity. This technique ensures preservation of posterior musculature, less blood loss, less postoperative pain and shorter hospital stay. Purpose: To evaluate efficacy of percutaneous pedicle screw fixation in the treatment of traumatic thoracolumbar fractures. Study design: Descriptive cohort clinical case study. Patients and Methods: Thirty patients aged 18 to 50 years, with thoracolumbar fractures (AO types A1, A2 & A3) and neurologically intact underwent percutaneous pedicle screw fixation using Medtronic longitude II system. Patients with kyphotic deformity >45o, body mass index (BMI) >30, or osteoporotic spine were excluded. Back pain scores on visual analogue scale (VAS) and radiological parameters (Cobb’s angle, vertebral height loss, and anterior vertebral wedging) were compared pre and postoperatively. At final follow up, clinical outcome was assessed based on modified Macnab criteria. Results: The mean operative time was 135 minutes, and the mean intraoperative blood loss was 115 ml. The average preoperative VAS score of back pain was 5 and improved to 2.8 postoperatively. Mean hospital stay was 4 days. Patients were followed up for 8 to 12 months. Preoperative mean Cobb’s angle was 10.8o and improved to 5.6o postoperatively. The rate of misplaced screws was 11.8%. Based on the modified Macnab criteria, the final clinical outcome was excellent in 12, good in 16, and fair in 2 patients with a general patient satisfaction rate (excellent to good recovery) of 93%. Conclusion: our data suggest that this minimally invasive technique is safe and effective treatment in AO type A thoracolumbar fractures without neurological compromise. (2017ESJ128)